2022
DOI: 10.22374/jeleu.v5i3.147
|View full text |Cite
|
Sign up to set email alerts
|

Diode Laser for the Management of Upper Tract Urothelial Cancer (UTUC) – Case Series.

Abstract: Background and Objective: Upper tract urothelial carcinoma (UTUC) is uncommon; however, at the time of diagnosis, they are usually more invasive than bladder urothelial carcinomas. Although nephroureterectomy (NU) has been the gold-standard treatment, guidelines have been set for kidney-sparing treatment in selected groups of patients. While these guidelines are aimed towards patients fit for salvage radical treatment, little has been published on managing the symptomatic patient not fit for NU. Various modali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Similarly, Martínez-Piñeiro et al [10] , in their retrospective case series of 19 cases, found a recurrence rate of 42.1%. They also reported a poorer prognosis for patients with ureteral tumors than those with renal pelvis [14] . This was attributed to ureteric location, concerns about inadvertent perforation, and poor visibility during endoscopic laser ablation.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, Martínez-Piñeiro et al [10] , in their retrospective case series of 19 cases, found a recurrence rate of 42.1%. They also reported a poorer prognosis for patients with ureteral tumors than those with renal pelvis [14] . This was attributed to ureteric location, concerns about inadvertent perforation, and poor visibility during endoscopic laser ablation.…”
Section: Discussionmentioning
confidence: 97%
“…Jimie et al [14] showed that management of UTUC with diode laser was safe and effective, providing symptom control in patients unfit for radical treatment. In their series, the authors reported its successful use in 63.3% of grade 2 tumors and 30% in grade 3 tumors, with an overall rate of 16.7% Clavien grade ≤2 complications, with no patient needing a blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations